2008
DOI: 10.1002/jbm.b.31232
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐computed tomographic analysis of bone healing subsequent to graft placement

Abstract: A micro-computed tomographic (muCT) analysis of bone healing subsequent to graft (tri calcium phosphate/TCP) placement in the maxillary sinus prior to dental endosteal implant placement was the focus of the current study. Ten trephined rod shaped human bone cores were obtained three months after the placement of particulate graft material. Using the muCT, samples were evaluated at 6 and 20 mum resolutions. The images exhibited regions of different grey scale (GL) magnitudes for bone and graft allowing a differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 18 publications
(44 reference statements)
1
23
0
Order By: Relevance
“…The following characteristics delineated NFB from the native bone: (1) absence of an organized lamellated appearance of mature bone; (2) increased cellularity and evidence of neovascularization; (3) random arrangement of osteocytes (as compared to being oriented with their long axes parallel to the lamellae in mature bone); and (4) more intense matrix stains with hematoxylin than with eosin (Figs. 3,4,5).…”
Section: Histological Analysismentioning
confidence: 98%
See 3 more Smart Citations
“…The following characteristics delineated NFB from the native bone: (1) absence of an organized lamellated appearance of mature bone; (2) increased cellularity and evidence of neovascularization; (3) random arrangement of osteocytes (as compared to being oriented with their long axes parallel to the lamellae in mature bone); and (4) more intense matrix stains with hematoxylin than with eosin (Figs. 3,4,5).…”
Section: Histological Analysismentioning
confidence: 98%
“…Based on histological findings in animal models, GBR using b-TCP promotes formation of new bone in osseous defect sites as early as 12 weeks [3,4]. Clinical studies evaluating GBR for maxillary sinus floor augmentation using b-TCP have shown evidence of integration of b-TCP to the native bone and newly formed bone (NFB) after 3 months based upon ex vivo micro-computed tomography (lCT) and histological findings [5,6].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Micro-CT has been used as a tool to investigate the 3D architecture of grafted bone [16][17][18][19], and it seems a practical method for investigating the gender differences (if any) in bone mineral density (BMD) and 3D trabecular architecture of grafted bone, especially for older patients. This study also examined the differences of BMD and 3D trabecular structure between the matured autogenous bone graft and the adjacent native bone.…”
Section: Introductionmentioning
confidence: 99%